Challenging conventional rural rail level crossing design: Evaluating three new systems thinking-based designs in a driving simulator. (December 2018) - Beanland, Vanessa; Grant, Eryn; Read, Gemma J.M.; Stevens, Nicholas; Thomas, Miles; Lenné, Michael G.; Stanton, Neville A.; Salmon, Paul M.
Highlights: 3 novel rail level crossing treatments were evaluated in a driving simulator. Designs used different approaches: in-vehicle speed guidance, low-cost warnings. Features were designed to make constraints more visible to drivers. Multiple measures illustrated that each design had strengths and weaknesses. Driving simulation provides a cost-effective means for testing design concepts. Abstract: The road-rail interface is hazardous for both road vehicles and trains, with collisions often resulting in serious injury and deaths of drivers and passengers. This is a major problem worldwide, and there is currently no appropriately effective low-cost solution for rural areas. Grade separation is prohibitively costly for most rail level crossings. This research evaluated three proposed new, relatively low-cost design solutions: GPS Average Speed interface, Simple but Strong crossing and Ecological Interface Design crossing. These new designs were compared with the conventional passive and active rural rail level crossings in a driving simulator. The findings suggest that there is a preference for the standard rail level crossings, probably because this is what drivers are used to. Of the new designs, the Ecological Interface Design rail level crossing seemed to perform the best in the simulator study, and could be implemented at a lower cost than conventional active rail level crossings. However, all three designs had apparent strengths and weaknesses. These findings highlight possible design solutions that should be further tested in real-world field trials.